PENGARUH MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP HASIL BELAJAR PADA MATA PELAJARAN SOSIOLOGI DI FASE F AWAL DI SMA NEGERI 1 SUNGAI TARAB - Hanivatul Rahmatillah; Faishal Yasin; Erningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the suboptimal use of learning media by teachers, which results in many students being distracted and not fully engaged in the learning process, leading to low learning outcomes in sociology subjects The theoretical framework of this study is based on cognitive theory, which emphasizes internal mental processes involved in understanding, remembering, and problem-solving. The main focus of this theory is on how individuals acquire, organize, store, and retrieve information.This research uses a quantitative approach with an experimental type. The research design employed is the Posttest-Only Control Design. Data collection techniques include questionnaires and multiple-choice tests. The data were analyzed using the t-test.The results indicate that there is a significant influence of technology-based learning media (X) on learning outcomes (Y). The significance value obtained is 0.038, which is smaller than the threshold of 0.05 (0.038 < 0.05), thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). This implies that technology-based learning media has a significant effect on students' learning outcomes. The regression model shows that for every one-unit increase in variable X, variable Y is predicted to increase by 1.080 units, with a significant intercept value of 53.452. Overall, there is a significant positive linear relationship between technology-based learning media and learning outcomes.